ZENON PRZESMYCKI I JEGO BRACIA WE WSPOMNIENIACH JAKUBA GIEWARTOWSKIEGO I DOKUMENTACH RODZINNYCH - Legutko, Grażyna (Colloquia Litteraria, 2025)
The article attempts to reconstruct the biographies of the three brothers of Zenon Przesmycki (‘Miriam’). Based on the analysis of source materials (memoirs of Jakub Giewartowski, documents and correspondence of the Przesmycki family), the author presents the history of Wojciech Tomasz, Tomasz Ignacy and Marian Adam Przesmycki. She moreover seeks to describe the mutual relations between Zenon and his brothers.